2006
DOI: 10.1007/s11194-006-9024-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sexual Arousal with Adolescent Males Who Have Offended Sexually: Self-Report and Unobtrusively Measured Viewing Time

Abstract: Sexual arousal was assessed using three approaches: the Affinity (Version. 1.0) computerized assessment of unobtrusively measured viewing time (VT), Affinity self-report ratings of sexual attractiveness, and a self-report sexual arousal graphing procedure. Data were collected from 78 males, aged 12–18 (M=15.09; SD=1.62), who acknowledged their sexual assaults. The pattern of responses to all three assessment techniques was remarkably similar, with maximal sexual interest demonstrated and reported for adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 42 publications
4
20
1
Order By: Relevance
“…First, this study did not include youth sexual offenders, a population vital to research investigating clinical utility. Second, although this study demonstrates that SCID exists in adolescents when assessed via the same methodologies as adult samples (VT), two recently published studies do not support the use of VT as a clinical tool with adolescents (Letourneau, 2002;Worling, 2006).…”
Section: Clinical Applicationcontrasting
confidence: 61%
See 1 more Smart Citation
“…First, this study did not include youth sexual offenders, a population vital to research investigating clinical utility. Second, although this study demonstrates that SCID exists in adolescents when assessed via the same methodologies as adult samples (VT), two recently published studies do not support the use of VT as a clinical tool with adolescents (Letourneau, 2002;Worling, 2006).…”
Section: Clinical Applicationcontrasting
confidence: 61%
“…Most studies have focused on determining if a particular measure can reliably differentiate adult participants by their sexual orientation and/or sexual age preference (e.g., individuals who have offended against children demonstrate significantly longer delays [in decision making] to images of children than adults) (Abel, Jordan, Hand, Holland, & Phipps, 2001;Gress, 2005;Harris et al, 1996;Worling, 2006). A few studies compared SCIDs of sexual offenders to non-sexual offenders (Beech et al, 2006;Smith & Waterman, 2004), and one study evaluated the difference between participants who self-reported either high sexual desire or low sexual desire (Giargiari et al, 2005).…”
mentioning
confidence: 99%
“…Apart from the introductory article by Glasgow et al (2003) and the validation study by Worling (2006), published empirical studies on Affinity are lacking. There are a couple of unpublished dissertations dealing with Affinity, however (Brown, 2005; Croxen, 2003; Loewinger Cloyd, 2007; Worsham, 2010).…”
Section: Viewing Time Assessmentmentioning
confidence: 99%
“…None of the control sample indicated any sexual interest in children in the questionnaire. Using the same version of the Affinity program as Worling (2006), Croxen (2003) noted internal consistency estimates (Cronbach’s α coefficients) ranging from .76 to .93. On a differential index of pedophilic interest (subtracting the maximum viewing times for the adult categories from the maximum viewing time for small children or juveniles), the mean of the child sexual abusers was 1.59 standard deviation units above the mean for the controls—a large and significant effect.…”
Section: Viewing Time Assessmentmentioning
confidence: 99%
“…Hudson and Ward (2000) have also hypothesized that deficits in social competency are central to sexual offending. In addition, child sexual abusers have been shown to have specialized atypical sexual interests (e.g., sexual interest in children) compared with other offenders and nonoffenders (e.g., Beech et al, 2008;Gray, Brown, MacCulloch, Smith, & Snowden, 2005;Worling, 2006). Various studies have found that child sexual abusers are less (or equally) prone to anger and hostility than other offender samples (e.g., Lee, Pattison, Jackson, & Ward, 2001;Overholser & Beck, 1986;Seidman, Marshall, Hudson, & Robertson, 1994;Yates & Kingston, 2006), with only one investigation showing that child sexual abusers report more (trait) anger than rapists (Kalichman, 1991).…”
mentioning
confidence: 99%